Effects of Diesel, Heavy Metals and Plastics Pollution on Penguins in Antarctica: A Review - Puasa, Nurul Aini; Zulkharnain, Azham; Verasoundarapandian, Gayathiri; Wong, Chiew-Yen; Zahri, Khadijah Nabilah Mohd; Merican, Faradina; Shaharuddin, Noor Azmi; Gomez Fuentes, Claudio German; Ahmad, Siti Aqlima (My University, 2021)
Simple Summary Antarctica is contaminated by anthropogenic pollution. Due to the persistent low temperatures, the toxic impacts of pollution to the environment can be extensive. The severity of the effects varies according to the animal species, chemical type and level of exposure. Penguins are at major risk as they are the most prominent group of animals in Antarctica. This review highlights the background of penguins in Antarctica, the anthropogenic pollution and cases, as well as the toxic effects of diesel, heavy metals and microplastics toward penguins. A bibliometric analysis is also included. Antarctica is a relatively pristine continent that attracts scientists and tourists alike. However, the risk of environmental pollution in Antarctica is increasing with the increase in the number of visitors. Recently, there has been a surge in interest regarding diesel, heavy metals and microplastics pollution. Contamination from these pollutants poses risks to the environment and the health of organisms inhabiting the continent. Penguins are one of the most prominent and widely distributed animals in Antarctica and are at major risk due to pollution. Even on a small scale, the impacts of pollution toward penguin populations are extensive. This review discusses the background of penguins in Antarctica, the anthropogenic pollution and cases, as well as the impacts of diesel, heavy metals and microplastics toxicities on penguins. The trends of the literature for the emerging risks of these pollutants are also reviewed through a bibliometric approach and network mapping analysis. A sum of 27 articles are analyzed on the effects of varying pollutants on penguins in Antarctica from 2000 to 2020 using the VOSviewer bibliometric software, Microsoft Excel and Tableau Public. Research articles collected from the Scopus database are evaluated for the most applicable research themes according to the bibliometric indicators (articles, geography distribution, annual production, integrated subject areas, key source journals and keyword or term interactions). Although bibliometric studies on the present research theme are not frequent, our results are sub-optimal due to the small number of search query matches from the Scopus database. As a result, our findings offer only a fragmentary comprehension of the topics in question. Nevertheless, this review provides valuable inputs regarding prospective research avenues for researchers to pursue in the future.
Keywords: antarctica; penguins; pollution; diesel; heavy metals; microplastics; toxicity